Fermentasi Tapai Ketan Hitam (Oryza sativa Linn var glutinosa): Fermentasi Tapai Ketan Hitam (Oryza sativa Linn var glutinosa) - Gres, Merzi Revi (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2023)
One of the black glutinous rice-based foods in Indonesia is fermented black glutinous rice (Oryza sativa Linn var glutinosa) which contains anthocyanins and phenols and has antioxidant effects. The purpose of this study was to determine the production process of fermented black glutinous rice. This type of research is experimental research. The results showed that in making tapai ketan hitam, the yeast and black glutinous rice must be balanced. The results of this study, before fermentation black glutinous rice black purple color, bland glutinous taste and no aroma. In black glutinous rice after fermentation black glutinous rice is still blackish purple, the combined taste is sweet, sour and slightly contains alhokol. There was also a distinctive aroma of tapai and a soft and slightly watery texture, and there was growth of mold mycelia attached to the sticky rice. The fungus that plays a role in fermentation in tape making is Saccharomyces cerevicae.